A corrosion-resistant metal coating agent and its preparation method and application

By mixing nickel powder, chromium powder and other materials in a specific proportion, and undergoing heat treatment and modification treatment, a corrosion-resistant metal coating agent with improved coordination was prepared, which solved the wear resistance and corrosion resistance of existing coating agents. The poor coordination in heat resistance and stability has achieved a comprehensive improvement in the performance of coating agents.

CN119020714BActive Publication Date: 2025-02-14GUANGZHOU MARITIME INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411137069.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-02-14
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

Existing metal coating agents have poor coordination in wear resistance, corrosion resistance and heat resistance, making it difficult to improve performance at the same time.

Method used

Coating agent with coordinated improvement is prepared by mixing nickel powder, chromium powder, regulatory functional modifier, tungsten powder, titanium carbide powder and yttrium lanthanum effector in a specific proportion, and a coating agent with coordinated improvement is prepared through heat treatment, modification treatment and other steps. .

Benefits of technology

It significantly improves the wear resistance, interface strength, corrosion resistance and heat stability of the coating agent, ensuring the stability of performance under different environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004999719280000131
    Figure BDA0004999719280000131
  • Figure BDA0004999719280000141
    Figure BDA0004999719280000141
Patent Text Reader

Abstract

The present invention relates to the field of metal coating technology, and specifically to a corrosion-resistant metal coating agent, a preparation method and application thereof. Among them, a preparation method of a corrosion-resistant metal coating agent comprises: mixing nickel powder, chromium powder, a regulating function modifier, tungsten powder, titanium carbide powder and yttrium lanthanum effector. The corrosion-resistant metal coating agent of the present invention contains nickel powder, chromium powder, tungsten powder and titanium carbide powder and yttrium lanthanum effector and regulating function modifier, wherein the yttrium lanthanum effector and the regulating function modifier cooperate to form a combined structure effect, which not only improves the wear resistance and interface strength performance of the product in a coordinated manner, but also significantly improves the corrosion resistance and heat resistance stability of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal coatings, and in particular to a corrosion-resistant metal coating agent and a preparation method and application thereof. Background Art

[0002] Coating refers to a thin layer of material that is attached to a certain base material and plays a special role and has a certain bonding strength with the base material. It can overcome certain defects of the base material and improve its surface properties, such as optical properties, electrical properties, erosion and corrosion resistance, wear resistance and mechanical strength. It is a thin film with a support. However, existing coatings have the problems of poor wear resistance, corrosion resistance, and heat resistance stability, as well as the difficulty in coordinating and improving wear resistance, interface bonding strength and other properties, which further limits the efficiency of product use. Summary of the invention

[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defects of existing metal coatings in terms of poor wear resistance, corrosion resistance and heat stability and difficulty in coordinating and improving wear resistance and interface strength properties, thereby providing a corrosion-resistant metal coating agent and its preparation method and application to solve the above problems.

[0004] In order to achieve the above object, the present invention provides the following technical solutions:

[0005] A method for preparing a corrosion-resistant metal coating agent comprises: mixing nickel powder, chromium powder, a regulating function modifier, tungsten powder, titanium carbide powder and a yttrium lanthanum effector;

[0006] The preparation method of the regulating function modifier comprises: heat-treating nano bentonite, immersing the heat-treated nano bentonite into a sodium dodecylbenzene sulfonate solution for a first modification to obtain a modified nano bentonite liquid, mixing the modified nano bentonite liquid with a silane coupling agent, citric acid, and chitosan solution for a second modification, and solid-liquid separation to obtain a nano bentonite agent, and immersing the nano bentonite agent into a modified performance liquid for a third modification, and solid-liquid separation to obtain the regulating function modifier; wherein the preparation method of the modified performance liquid comprises: mixing flaky talc powder, a sodium silicate solution, and a phosphate buffer solution to obtain a flaky talc agent; performing a fourth modification on hydroxyapatite, nano silica sol, and a sodium citrate solution, and solid-liquid separation to obtain a hydroxyapatite body; mixing the hydroxyapatite body with the flaky talc agent to obtain a modified performance liquid;

[0007] The preparation method of the yttrium lanthanum effect agent comprises: irradiating silicon carbide whiskers, immersing the irradiated silicon carbide whiskers in a potassium permanganate solution for reaction, and performing solid-liquid separation to obtain a silicon carbide whisker agent; mixing a lanthanum nitrate solution, a sodium lignin sulfonate solution and a silane coupling agent to obtain a lanthanum liquid matrix agent; and mixing the lanthanum liquid matrix agent, yttrium oxide and a silicon carbide whisker agent to obtain a yttrium lanthanum effect agent.

[0008] Preferably, the mass ratio of the nickel powder, chromium powder, regulating function modifier, tungsten powder, titanium carbide powder and yttrium lanthanum effector is (20-25): (10-15): (6-9): (5-8): (4-7): (3-5);

[0009] And / or, the process of heat treatment of the nano bentonite is: first heat treatment of the nano bentonite at 125-135°C for 5-10 min, then heating to 350°C at a rate of 2-5°C / min and keeping warm for 5 min, then cooling to 55°C at a rate of 1-3°C / min and keeping warm for standby use;

[0010] And / or, the mass fraction of the sodium dodecylbenzenesulfonate solution is 5%;

[0011] And / or, the mass ratio of the heat-treated nano-bentonite to the sodium dodecylbenzene sulfonate solution is 1:(10-15).

[0012] Preferably, the mass ratio of the modified nano-bentonite solution to the silane coupling agent, citric acid, and chitosan solution is (5-9): (2-4): (1-3): (3-7);

[0013] And / or, the silane coupling agent is KH550 or KH560;

[0014] And / or, the mass fraction of the chitosan solution is 2-5%;

[0015] And / or, the first modification treatment is ultrasonic oscillation treatment; the power of the ultrasonic oscillation treatment is 350-400W, and the time of the ultrasonic oscillation treatment is 20-30min;

[0016] And / or, the second modification treatment is ball milling; the rotation speed of the ball milling is 1000-1500r / min, and the time of the ball milling is 1-2h;

[0017] And / or, the third modification treatment is a stirring treatment; the stirring speed is 550-750r / min, and the stirring time is 45min;

[0018] And / or, the mass ratio of the nano bentonite agent to the modified performance liquid is 2:5.

[0019] Preferably, the mass ratio of the flaky talc powder, the sodium silicate solution, and the phosphate buffer solution is (5-8): (2-5): (4-7);

[0020] And / or, the mass fraction of the sodium silicate solution is 5%;

[0021] And / or, the pH value of the phosphate buffer solution is 5.5;

[0022] And / or, the mass fraction of the sodium citrate solution is 4-8%;

[0023] And / or, the mass ratio of the hydroxyapatite, nano-silica sol and sodium citrate solution is 4:1:6;

[0024] And / or, the mass ratio of the hydroxyapatite to the flaky talc is 2:5;

[0025] And / or, the fourth modification treatment is ball milling; the rotation speed of the ball milling is 1100-1200r / min, and the time of the ball milling is 2h;

[0026] And / or, drying is further performed after the solid-liquid separation.

[0027] Preferably, the irradiation treatment is proton irradiation treatment;

[0028] And / or, the power of the irradiation treatment is 350-400W;

[0029] And / or, the duration of the irradiation treatment is 5-10 min;

[0030] And / or, the mass fraction of the potassium permanganate solution is 5%;

[0031] And / or, the mass fraction of the lanthanum nitrate solution is 2-5%;

[0032] And / or, the mass fraction of the sodium lignin sulfonate solution is 3-6%.

[0033] Preferably, the mass ratio of the lanthanum nitrate solution, the sodium lignin sulfonate solution and the silane coupling agent is (3-5): (1-3): (1-2);

[0034] And / or, the mass ratio of the lanthanum liquid matrix agent, yttrium oxide and silicon carbide whisker agent is (5-8): (2-4): (2-5).

[0035] The present invention also provides a corrosion-resistant metal coating agent, which is prepared by the above-mentioned method for preparing the corrosion-resistant metal coating agent.

[0036] The present invention also provides application of the above-mentioned corrosion-resistant metal coating agent on a metal base material.

[0037] Preferably, the applying step comprises: spraying the corrosion-resistant metal coating agent onto the surface of the metal base material to form a coating body.

[0038] Preferably, the spraying is arc spraying; the conditions of arc spraying are: voltage 20-22V, current 150-180A, spraying distance 100-120mm;

[0039] And / or, the metal matrix material is an iron matrix material;

[0040] And / or, the coating body has a thickness of 1-2 mm.

[0041] In the present invention, the time for mixing the hydroxyapatite and the flaky talc is 20-30 minutes.

[0042] The technical solution of the present invention has the following advantages:

[0043] A method for preparing a corrosion-resistant metal coating agent comprises: mixing nickel powder, chromium powder, a regulating function modifier, tungsten powder, titanium carbide powder and yttrium lanthanum effectiveness agent; the method for preparing the regulating function modifier comprises: heat-treating nano-bentonite, immersing the heat-treated nano-bentonite in a sodium dodecylbenzene sulfonate solution for a first modification to obtain a modified nano-bentonite liquid, mixing the modified nano-bentonite liquid with a silane coupling agent, citric acid and chitosan solution for a second modification, solid-liquid separation to obtain a nano-bentonite agent, immersing the nano-bentonite agent in a modified effectiveness liquid for a third modification, solid-liquid separation to obtain the regulating function modifier; wherein the preparation of the modified effectiveness liquid The method comprises: mixing flaky talc powder, sodium silicate solution and phosphate buffer solution to obtain flaky talc powder; performing a fourth modification treatment on hydroxyapatite, nano silica sol and sodium citrate solution, and performing solid-liquid separation to obtain a hydroxyapatite body; and mixing the hydroxyapatite body with the flaky talc powder to obtain a modified performance liquid. The preparation method of the yttrium lanthanum performance agent comprises: performing irradiation treatment on silicon carbide whiskers, immersing the irradiated silicon carbide whiskers in a potassium permanganate solution for reaction, and performing solid-liquid separation to obtain a silicon carbide whisker agent; mixing a lanthanum nitrate solution, a sodium lignin sulfonate solution and a silane coupling agent to obtain a lanthanum liquid matrix agent; and mixing the lanthanum liquid matrix agent, yttrium oxide and a silicon carbide whisker agent to obtain a yttrium lanthanum performance agent.

[0044] The corrosion-resistant metal coating agent of the present invention contains nickel powder, chromium powder, tungsten powder and titanium carbide powder, yttrium lanthanum effector and regulating function modifier, wherein the yttrium lanthanum effector and regulating function modifier cooperate with each other to form a combined effect, which not only improves the wear resistance and interface strength performance of the product in a coordinated manner, but also significantly improves the corrosion resistance and heat resistance stability of the product. In the process of obtaining the regulating function modifier, the present invention first heat-treats the nano-bentonite to optimize the interlayer spacing and active efficiency of the nano-bentonite, then forms a modified nano-bentonite liquid by combining with a sodium dodecylbenzene sulfonate solution, and then further modifies the nano-bentonite agent with a silane coupling agent, citric acid, and a chitosan solution, so that the obtained nano-bentonite agent can better coordinate and improve with the modified efficiency liquid; the modified efficiency liquid is mixed with flaky talc, a sodium silicate solution, and a phosphate buffer solution to obtain a flaky talc agent, and hydroxyapatite is reacted with a nano-silica sol and a sodium citrate solution to prepare a hydroxyapatite body, and then the hydroxyapatite body is coordinated and immersed in the flaky talc agent to obtain the obtained product. When the nano-bentonite agent is mixed and modified with the modified efficiency liquid, the flaky talc and the nano-bentonite are assembled into a flaky nano-bentonite to enhance the performance coordination and product stability of the product, and the hydroxyapatite body is combined to further improve the performance of the product. The yttrium lanthanum active agent is prepared by irradiating silicon carbide whiskers and treating them with potassium permanganate solution to optimize their activity performance. The lanthanum liquid matrix agent is then obtained by a mixed reaction of lanthanum nitrate solution, sodium lignin sulfonate solution and silane coupling agent. The lanthanum liquid matrix agent is then coordinated and synergized with yttrium oxide and silicon carbide whiskers to further enhance the performance of the product through the whisker structure distribution system. DETAILED DESCRIPTION

[0045] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0046] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0047] Example 1

[0048] This embodiment provides a method for preparing a corrosion-resistant metal coating agent, and the specific steps are as follows:

[0049] 1) Obtaining a modified performance liquid: Weighing 5 parts by weight of flaky talc, 2 parts by weight of a 5% sodium silicate solution, and 4 parts by weight of a phosphate buffer solution with a pH value of 5.5, and mixing and stirring them uniformly to obtain a flaky talc agent; mixing hydroxyapatite, nano-silica sol, and a 4% sodium citrate solution in a weight ratio of 4:1:6, and ball milling (ball milling speed of 1100 r / min, ball milling time of 2 h), filtering, and drying to obtain a hydroxyapatite body; immersing the hydroxyapatite body in a weight ratio of 2:5 (immersion power of 400 W, immersion time of 20 min) into the flaky talc agent to fully obtain a modified performance liquid;

[0050] 2) Obtaining a regulating function modifier: first heat-treating the nano-bentonite at 125°C for 5 minutes, then heating to 350°C at a rate of 2°C / min, keeping the temperature for 5 minutes, and then cooling to 55°C at a rate of 1°C / min, keeping the temperature for standby use; immersing the nano-bentonite in a sodium dodecylbenzene sulfonate solution with a mass ratio of 1:10, and ultrasonically oscillating the nano-bentonite (oscillating power of 350W, oscillating time of 20min) to obtain a modified nano-bentonite. Soil liquid, 5 parts by weight of modified nano bentonite liquid, 2 parts by weight of silane coupling agent KH560, 1 part by weight of citric acid, and 3 parts by weight of chitosan solution with a mass fraction of 2% are mixed and ball-milled (ball-milled at a speed of 1000r / min for 1h), filtered, washed with water, and dried to obtain a nano bentonite agent; then the nano bentonite agent and the modified efficiency liquid obtained in step 1) are mixed and stirred at a weight ratio of 2:5 (stirring speed is 550r / min, stirring time is 45min), filtered, washed with water, and dried to obtain an adjustable function modifier;

[0051] 3) Obtaining a yttrium lanthanum effector: first irradiating a silicon carbide whisker in a proton irradiation box at a power of 350 W for 5 minutes, then placing the irradiated silicon carbide whisker in a sufficient amount of a 5% potassium permanganate solution, stirring and mixing, then filtering, washing and drying to obtain a silicon carbide whisker; weighing 3 parts by weight of a 2% lanthanum nitrate solution, 1 part by weight of a 3% sodium lignin sulfonate solution and 1 part by weight of a silane coupling agent KH550, blending them to obtain a lanthanum liquid matrix agent; weighing 5 parts by weight of a lanthanum liquid matrix agent, 2 parts by weight of yttrium oxide and 2 parts by weight of a silicon carbide whisker agent, blending them to obtain a yttrium lanthanum effector;

[0052] 4) Weigh 20 parts by weight of nickel powder, 10 parts by weight of chromium powder, 6 parts by weight of the regulating function modifier obtained in step 2), 5 parts by weight of tungsten powder, 4 parts by weight of titanium carbide powder and 3 parts by weight of the yttrium lanthanum effector obtained in step 3), mix the above raw materials evenly, then ball mill at a speed of 1500 r / min for 2 hours, and obtain a coating agent after drying.

[0053] The coating agent prepared in this embodiment is sprayed onto the surface of a metal iron substrate by arc spraying technology to form a coating body, thereby obtaining the corrosion-resistant metal coating of the present invention. The coating body thickness is 1 mm, and the spraying conditions are: voltage 20 V, current 150 A, and spraying distance 100 mm.

[0054] Example 2

[0055] This embodiment provides a method for preparing a corrosion-resistant metal coating agent, and the specific steps are as follows:

[0056] 1) Obtaining a modified performance liquid: Weighing 8 parts by weight of flaky talc, 5 parts by weight of a 5% sodium silicate solution, and 7 parts by weight of a phosphate buffer solution with a pH value of 5.5, and blending and stirring them evenly to obtain a flaky talc agent; mixing hydroxyapatite, nano-silica sol, and a sodium citrate solution with a mass fraction of 8% in a weight ratio of 4:1:6, and ball milling (ball milling speed of 1200r / min, ball milling time of 2h), filtering, and drying to obtain a hydroxyapatite body; immersing the hydroxyapatite body in a weight ratio of 2:5 (immersion power of 500W, immersion time of 30min) into the flaky talc agent to fully obtain a modified performance liquid;

[0057] 2) Obtaining a regulating function modifier: first heat-treating the nano-bentonite at 135°C for 10 min, then heating to 350°C at a rate of 5°C / min, keeping the temperature for 5 min, and then cooling to 55°C at a rate of 3°C / min, keeping the temperature for later use; immersing the nano-bentonite in a sodium dodecylbenzene sulfonate solution having a mass ratio of 1:15 and ultrasonically oscillating the solution (oscillating power of 400 W, oscillating time of 30 min) to obtain a modified nano-bentonite Soil liquid, 9 parts by weight of modified nano bentonite liquid, 4 parts by weight of silane coupling agent KH560, 3 parts by weight of citric acid, and 7 parts by weight of chitosan solution with a mass fraction of 5% are mixed and ball-milled (ball-milled at a speed of 1500r / min for 2h), filtered, washed with water, and dried to obtain a nano bentonite agent; then the nano bentonite agent and the modified efficiency liquid obtained in step 1) are mixed and stirred at a weight ratio of 2:5 (stirring speed is 750r / min, stirring time is 45min), filtered, washed with water, and dried to obtain an adjustable function modifier;

[0058] 3) Obtaining a yttrium lanthanum effector: first irradiating a silicon carbide whisker in a proton irradiation box at a power of 400 W for 10 min, then placing the irradiated silicon carbide whisker in a sufficient amount of a 5% potassium permanganate solution, stirring and mixing, then filtering, washing and drying to obtain a silicon carbide whisker; weighing 5 parts by weight of a 5% lanthanum nitrate solution, 3 parts by weight of a 6% sodium lignin sulfonate solution and 2 parts by weight of a silane coupling agent KH550, blending them to obtain a lanthanum liquid matrix agent; weighing 8 parts by weight of a lanthanum liquid matrix agent, 4 parts by weight of yttrium oxide and 5 parts by weight of a silicon carbide whisker agent, blending them to obtain a yttrium lanthanum effector;

[0059] 4) Weigh 25 parts by weight of nickel powder, 15 parts by weight of chromium powder, 9 parts by weight of the regulating function modifier obtained in step 2), 8 parts by weight of tungsten powder, 7 parts by weight of titanium carbide powder and 5 parts by weight of the yttrium lanthanum effector obtained in step 3), mix the above raw materials evenly, then ball mill at a speed of 1500 r / min for 2 h, and obtain a coating agent after drying.

[0060] The coating agent prepared in this embodiment is sprayed onto the surface of a metal iron substrate by arc spraying technology to form a coating body, thereby obtaining the corrosion-resistant metal coating of the present invention. The coating body thickness is 2 mm, and the spraying conditions are: voltage 22 V, current 180 A, and spraying distance 120 mm.

[0061] Example 3

[0062] This embodiment provides a method for preparing a corrosion-resistant metal coating agent, and the specific steps are as follows:

[0063] 1) Obtaining a modified performance liquid: Weighing 6.5 parts by weight of flaky talc, 3.5 parts by weight of a 5% sodium silicate solution, and 5.5 parts by weight of a phosphate buffer solution with a pH value of 5.5, and mixing and stirring them uniformly to obtain a flaky talc agent; mixing hydroxyapatite, nano-silica sol, and a 6% sodium citrate solution in a weight ratio of 4:1:6, and ball milling (ball milling speed of 1150r / min, ball milling time of 2h), filtering, and drying to obtain a hydroxyapatite body; immersing the hydroxyapatite body in a weight ratio of 2:5 (immersion power of 450W, immersion time of 25min) into the flaky talc agent to fully obtain a modified performance liquid;

[0064] 2) Obtaining a regulating function modifier: first heat-treating the nano-bentonite at 130°C for 7.5 min, then heating to 350°C at a rate of 3.5°C / min, keeping warm for 5 min, and then cooling to 55°C at a rate of 2°C / min, keeping warm for standby use; immersing the nano-bentonite in a sodium dodecylbenzene sulfonate solution with a mass ratio of 1:12 and ultrasonically oscillating the solution (oscillating power of 370 W, oscillating time of 25 min) to obtain a modified nano-bentonite liquid, 6.5 parts by weight of modified nano-bentonite liquid, 3 parts by weight of silane coupling agent KH560, 2 parts by weight of citric acid, and 5 parts by weight of chitosan solution with a mass fraction of 3.5% are mixed and ball-milled (ball-milled at a speed of 1250r / min for 1.5h), filtered, washed with water, and dried to obtain a nano-bentonite agent; then the nano-bentonite agent and the modified efficiency liquid obtained in step 1) are mixed and stirred at a weight ratio of 2:5 (stirring speed is 600r / min, stirring time is 45min), filtered, washed with water, and dried to obtain an adjustable function modifier;

[0065] 3) Obtaining a yttrium lanthanum effector: irradiating a silicon carbide whisker in a proton irradiation box at a power of 370 W for 7.5 min, then placing the irradiated silicon carbide whisker in a sufficient amount of a 5% potassium permanganate solution, stirring and mixing, then washing and drying to obtain a silicon carbide whisker; weighing 4 parts by weight of a 3.5% lanthanum nitrate solution, 2 parts by weight of a 4.5% sodium lignin sulfonate solution and 1.5 parts by weight of a silane coupling agent KH550, blending them to obtain a lanthanum liquid matrix agent; weighing 6.5 parts by weight of a lanthanum liquid matrix agent, 3 parts by weight of yttrium oxide and 3.5 parts by weight of a silicon carbide whisker agent, blending them to obtain a yttrium lanthanum effector;

[0066] 4) Weigh 22.5 parts by weight of nickel powder, 12.5 parts by weight of chromium powder, 7.5 parts by weight of the regulating function modifier obtained in step 2), 6.5 parts by weight of tungsten powder, 5.5 parts by weight of titanium carbide powder and 4 parts by weight of the yttrium lanthanum effector obtained in step 3), mix the above raw materials evenly, then ball mill at a speed of 1500 r / min for 2 h, and obtain a coating agent after drying.

[0067] The coating agent prepared in this embodiment is sprayed onto the surface of a metal iron substrate by arc spraying technology to form a coating body, thereby obtaining the corrosion-resistant metal coating of the present invention. The coating body thickness is 1.5 mm, and the spraying conditions are: voltage 21 V, current 165 A, and spraying distance 110 mm.

[0068] Comparative Example 1

[0069] The difference between this comparative example and Example 3 is that no regulating function modifier is added to the coating agent, and other conditions are the same as those in Example 3.

[0070] Comparative Example 2

[0071] The difference between this comparative example and Example 3 is that, in the process of obtaining the regulating function modifier, the nano bentonite is not subjected to heat treatment and the first modification treatment, and the other conditions are the same as those in Example 3.

[0072] Comparative Example 3

[0073] The difference between this comparative example and Example 3 is that, in the process of obtaining the regulating function modifier, the modified nano-bentonite is not subjected to the second modification treatment, and the other conditions are the same as those in Example 3.

[0074] Comparative Example 4

[0075] The difference between this comparative example and Example 3 is that, in the process of obtaining the regulating function modifier, the nano bentonite is not subjected to heat treatment, and other conditions are the same as those in Example 3.

[0076] Comparative Example 5

[0077] The difference between this comparative example and Example 3 is that, in the process of obtaining the regulating functional modifier, no silane coupling agent and citric acid are added in the second modification treatment, and other conditions are the same as those in Example 3.

[0078] Comparative Example 6

[0079] The difference between this comparative example and Example 3 is that, in the process of obtaining the regulating function modifier, no modified efficiency liquid is added, and other conditions are the same as those in Example 3.

[0080] Comparative Example 7

[0081] The difference between this comparative example and Example 3 is that no yttrium lanthanum activator is added to the coating agent, and other conditions are the same as those in Example 3.

[0082] Comparative Example 8

[0083] The difference between this comparative example and Example 3 is that, in the process of obtaining the yttrium lanthanum effector, no silicon carbide whisker agent is added, and other conditions are the same as those in Example 3.

[0084] Comparative Example 9

[0085] The difference between this comparative example and Example 3 is that, in the process of obtaining the yttrium lanthanum activator, no yttrium oxide and lanthanum nitrate solution are added, and other conditions are the same as those in Example 3.

[0086] Comparative Example 10

[0087] The difference between this comparative example and Example 3 is that, in the process of obtaining the yttrium lanthanum active agent, no sodium lignin sulfonate solution and silane coupling agent KH550 are added, and other conditions are the same as those in Example 3.

[0088] Comparative Example 11

[0089] The difference between this comparative example and Example 3 is that, in the process of obtaining the modified performance liquid, no hydroxyapatite is added, and other conditions are the same as those in Example 3.

[0090] Comparative Example 12

[0091] The difference between this comparative example and Example 3 is that in the process of obtaining the modified performance liquid, no nano-silica sol and sodium citrate solution are added in the process of preparing the hydroxyapatite body, that is, the fourth modification treatment is not performed, and other conditions are the same as those in Example 3.

[0092] Comparative Example 13

[0093] The difference between this comparative example and Example 3 is that, in the process of obtaining the modified performance liquid, no flaky talc is added to the flaky talc agent, and other conditions are the same as those in Example 3.

[0094] Comparative Example 14

[0095] The difference between this comparative example and Example 3 is that, in the process of obtaining the modified performance liquid, no sodium silicate solution is added to the flaky talc, and other conditions are the same as those in Example 3.

[0096] Test Example 1

[0097] The products of the embodiment and the comparative example were tested for their interface strength and wear resistance under normal conditions. At the same time, the products were placed in a 2% sodium chloride salt spray condition for 24 hours, and then placed at 65°C for 12 hours. After the above operation was repeated 10 times, the corrosion resistance and temperature stability of the products were tested. The performance measurement results are shown in Table 1.

[0098] Table 1

[0099]

[0100]

[0101] According to the test results in Table 1, compared with the comparative example, the friction resistance and interface bonding strength of the product treated with the coating agent prepared in the embodiment of the present invention are significantly improved, achieving coordinated improvement in the wear resistance and interface strength performance of the product. Moreover, compared with conventional conditions, the friction resistance and interface bonding strength of the product treated with the coating agent prepared in the present invention under corrosion and high temperature conditions are not significantly reduced, that is, the performance stability effect of the product treated with the coating agent prepared in the embodiment of the present invention is very significant.

[0102] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a corrosion-resistant metal coating agent, characterized in that: include: The nickel powder, chromium powder, regulating function modifier, tungsten powder, titanium carbide powder and yttrium lanthanum effector are mixed and obtained; The preparation method of the regulating function modifier comprises: heat-treating nano bentonite, immersing the heat-treated nano bentonite into a sodium dodecylbenzene sulfonate solution for a first modification to obtain a modified nano bentonite liquid, mixing the modified nano bentonite liquid with a silane coupling agent, citric acid, and chitosan solution for a second modification, and solid-liquid separation to obtain a nano bentonite agent, and immersing the nano bentonite agent into a modified performance liquid for a third modification, and solid-liquid separation to obtain the regulating function modifier; wherein the preparation method of the modified performance liquid comprises: mixing flaky talc powder, a sodium silicate solution, and a phosphate buffer solution to obtain a flaky talc agent; performing a fourth modification on hydroxyapatite, nano silica sol, and a sodium citrate solution, and solid-liquid separation to obtain a hydroxyapatite body; mixing the hydroxyapatite body with the flaky talc agent to obtain a modified performance liquid; The preparation method of the yttrium lanthanum effect agent comprises: irradiating silicon carbide whiskers, immersing the irradiated silicon carbide whiskers in a potassium permanganate solution for reaction, and performing solid-liquid separation to obtain a silicon carbide whisker agent; mixing a lanthanum nitrate solution, a sodium lignin sulfonate solution and a silane coupling agent to obtain a lanthanum liquid matrix agent; and mixing the lanthanum liquid matrix agent, yttrium oxide and a silicon carbide whisker agent to obtain a yttrium lanthanum effect agent.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the nickel powder, chromium powder, regulating function modifier, tungsten powder, titanium carbide powder and yttrium lanthanum effector is (20-25): (10-15): (6-9): (5-8): (4-7): (3-5); And / or, the process of heat treatment of the nano bentonite is: first heat treatment of the nano bentonite at 125-135°C for 5-10 min, then heating to 350°C at a rate of 2-5°C / min and keeping warm for 5 min, then cooling to 55°C at a rate of 1-3°C / min and keeping warm for standby use; And / or, the mass fraction of the sodium dodecylbenzenesulfonate solution is 5%; And / or, the mass ratio of the heat-treated nano-bentonite to the sodium dodecylbenzene sulfonate solution is 1:(10-15).

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the modified nano-bentonite solution to the silane coupling agent, citric acid, and chitosan solution is (5-9): (2-4): (1-3): (3-7); And / or, the silane coupling agent is KH550 or KH560; And / or, the mass fraction of the chitosan solution is 2-5%; And / or, the first modification treatment is ultrasonic oscillation treatment; And / or, the second modification treatment is ball milling; And / or, the third modification treatment is a stirring treatment; And / or, the mass ratio of the nano bentonite agent to the modified performance liquid is 2:

5.

4. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the flaky talc powder, the sodium silicate solution and the phosphate buffer solution is (5-8): (2-5): (4-7); And / or, the mass fraction of the sodium silicate solution is 5%; And / or, the pH value of the phosphate buffer solution is 5.5; And / or, the mass fraction of the sodium citrate solution is 4-8%; And / or, the mass ratio of the hydroxyapatite, nano-silica sol and sodium citrate solution is 4:1:6; And / or, the mass ratio of the hydroxyapatite to the flaky talc is 2:5; And / or, the fourth modification treatment is ball milling; And / or, drying is performed after the solid-liquid separation.

5. The preparation method according to claim 1 or 2, characterized in that: The irradiation treatment is proton irradiation treatment; And / or, the power of the irradiation treatment is 350-400W; And / or, the duration of the irradiation treatment is 5-10 min; And / or, the mass fraction of the potassium permanganate solution is 5%; And / or, the mass fraction of the lanthanum nitrate solution is 2-5%; And / or, the mass fraction of the sodium lignin sulfonate solution is 3-6%.

6. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the lanthanum nitrate solution, the sodium lignin sulfonate solution and the silane coupling agent is (3-5): (1-3): (1-2); And / or, the mass ratio of the lanthanum liquid matrix agent, yttrium oxide and silicon carbide whisker agent is (5-8): (2-4): (2-5).

7. A corrosion-resistant metal coating agent, characterized in that: The corrosion-resistant metal coating agent is prepared by the preparation method of the corrosion-resistant metal coating agent described in any one of claims 1 to 6.

8. Use of the corrosion-resistant metal coating agent according to claim 7 on a metal substrate material.

9. The use according to claim 8, characterized in that: The application steps include: spraying the corrosion-resistant metal coating agent onto the surface of the metal base material to form a coating body.

10. The use according to claim 9, characterized in that: The spraying is arc spraying; And / or, the metal matrix material is an iron matrix material; And / or, the coating body has a thickness of 1-2 mm.

Citation Information

Patent Citations

  • Hard alloy cutter surface coating and preparation method thereof

    CN118437928A

  • Modified metal compositions and methods related thereto

    WO2022038508A1